The Homilies on Mishnah and Talmud Study at the Close of Bavli Bava’ Metsi‘a’ 2 and Yerushalmi Horayot 3: Their Origin and Development - Amit, Aaron (The Jewish quarterly review, 2012)
The final sugya of the second chapter of bBM II bears a striking similarity to the final sugya of the third chapter of yHor. Careful comparison of the two units demonstrates that the closing unit in bBM owes its genesis to the parallel material in yHor. The detailed two-part discussion in the Yerushalmi was condensed in the Bavli into two shorter parallel units, one concentrating on the relationship of the various fields of endeavor to one another, and the other focusing on an aggadic discussion of the importance of Talmud and the preference for the sage over the simpleton. , Our analysis of this sugya has important ramifications for Bavli and Yerushalmi scholarship. Our study shows that the editor of the Bavli expanded short tannaitic units, which were correctly attributed to tannaim, by augmenting them with related amoraic material, showing the importance of using parallel sugyot to confirm or reject the authenticity of attributed material in the Talmudim, and explaining how inauthentic attributed material can be generated. Our analysis also indicates that just as the opening passages of chapters and tractates have unique qualities because they are a crucial locus for halakhic- and savoraic- type discussions, the ends of chapters or of tractates likewise have unique qualities, for precisely the opposite reason: a dearth of organically relevant halakhic material led the editors to seek aggadic material taken from elsewhere to augment the discussions of the final mishnayot in a tractate or chapter, enabling the unit to end on an edifying note.